Spatial Analysis of the Paved Road Network in the City of Bani Walid : A Study in Transport Geography Using (GIS) (Journal of Libya for geographical studies, 2025)
The road network is one of the fundamental components of urban infrastructure, playing a crucial role in facilitating transportation, promoting economic and social development, and supporting urban growth. This study aims to evaluate the efficiency of the paved road network in the city of Bani Walid using Geographic Information Systems (GIS). It relies on spatial data analysis of the road network and population density, examining the spatial distribution of roads and the extent to which it meets residents’ needs.This study holds particular importance for Bani Walid, where several neighborhoods suffer from a lack of adequate road infrastructure, affecting access to essential services such as schools and hospitals. The research seeks to analyze the relationship between population density and road network distribution, with a focus on the influence of geographical factors on the network.The methodology included the collection and analysis of field data using GIS tools. A regional approach was adopted to highlight the geographic features of the city and the distribution of roads across its urban districts, while an analytical approach was used to examine data patterns and relationships within the road network. The study concludes with a set of recommendations aimed at improving and developing the road network to better meet the city’s future needs.
Keywords: Road network; Bani Walid city; GIS; Spatial analysis